Effects of DEM Resolution on Hydrological Connectivity Index of Small Watershed in Intensive Sugarcane Area - Kang Zhenwei; Li Yong; Huang Zhigang; Ming Xue (Shuitu baochi tongbao)
[Objective] The response of surface microtopography characteristic index, and hydrological connectivity (IC) index to different resolutions of digital elevation model (DEM) was studied, and the best DEM resolution of IC was determined in a small watershed of an intensive sugarcane production area in order to provide a theoretical basis and reference for subsequent research on hydrological connectivity, agricultural non-point source pollution, and soil erosion. [Methods] The effects of different resolutions of DEM (0.05, 0.1, 0.2, 0.5, 1, 2, and 5 m) on surface microtopography characteristics 〔slope (S), slope length (L), surface roughness (SR), standard deviation of elevation (SDE), and IC〕 were studied in an intensive sugarcane planting area in Southern China using ArcGIS and high-resolution images from an unmanned aerial vehicle (UAV). [Results] ① A decrease in pixel size (5—0.05 m) increased mean S and SR by 29.13% and 1.62%, respectively, but decreased mean SDE and L by 98.72% and 72.09%, respectively. The decreased resolution increased the mean S of newly planted sugarcane, perennial sugarcane, newly planted sugarcane+watermelon, and Eucalyptus, but decreased their L. In contrast, their SR first decreased at 5—1 m and then increased at 1—0.05 m, while SDE decreased generally. However, the S and SR of the road decreased first at 5—1 m and then increased at 1—0.05 m, while L of the river increased first at 5—2 m, and thereafter decreased at 2—0.05 m. ② Mean IC increased first at 5—0.2 m, and then decreased at 0.2—0.05 m. The difference in mean IC of different land use types reached its maximum value (34.72%) at 0.5 m. At 0.1 m resolution, IC followed the order of river>newly planted sugarcane>newly planted sugarcane+watermelon>perennial sugarcane>road>Eucalyptus. The best DEM resolution for Eucalyptus, roads, and rivers was 0.5 m, while 0.1 m resolution was best suited for newly planted sugarcane, perennial sugarcane, and newly planted sugarcane+watermelon. ③ The best DEM resolution for a small watershed in an intensive sugarcane area was 0.1 m. [Conclusion] DEM resolution had a significant effect on IC and index of surface microtopography characteristics, with varied effects for different land use types. The optimal DEM resolution of 0.1 m was best suitable for the characterization of a small watershed in an intensive sugarcane area.